Kesesuaian pelaksanaan Program Pendidikan Khas di Politeknik Johor Bahru - Kamaruzaman, Nurulziha (2009)
This study was conducted to determine suitability of implementation the teaching and learning process in Special Education Program (SEP) in polytechnics. Research domains that were studied are lecturers’ skill, acceptance of educational institute towards the capabilities of the disable students, suitability infrastructures and curriculum. Respondents for this research were 30 lecturers that align with learning process of the disable student that involved in the SEP program in Politeknik Johor Bahru (Johor). Questionnaires are used as the main research instrument. Data was analyzed with SPSS (Statistic Package for the Social Science) version 15.0. Alpha Cronbach () value for this research is 0.70. The mean score and percentages were used to analyze about the suitability of the factors. The findings revealed that, lecturers’ skills and suitability of the curriculum of the SEP programs plays important roles in the development and achievement of the disable students. The level of acceptance towards these groups of learners in educational institution of disable students and the infrastructures available which suit them are at medium level. Overall, the findings indicated that the effectiveness of Special Education Program (SEP) in polytechnics is affected by the link between the ministry and the lecturers.